2005
DOI: 10.1021/jm0490888
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of 11-Substituted 6-Aminobenzo[c]phenanthridine Derivatives, a New Class of Antitumor Agents

Abstract: The synthesis of 11-substituted 6-amino-11,12-dihydrobenzo[c]phenanthridines and 11-substituted 6-aminobenzo[c]phenanthridines through an efficient method is described. The antiproliferative activity of selected compounds against a wide panel of tumor cell lines was tested in the in vitro anticancer screening and the in vivo hollow fiber assay of the National Cancer Institute. Several compounds turned out to exhibit considerable cytotoxicity for tumor cells. For the study of structure-activity relationships di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(55 citation statements)
references
References 17 publications
1
52
0
2
Order By: Relevance
“…[1][2][3] In addition, it was shown that the chemical modulation of the ethidium substituents is a profitable option to tune the nucleic acid recognition properties of phenanthridine dyes. [4] Very recent reports about numerous applications point toward versatility of the phenanthridine core, [5][6][7][8][9] including even intriguing biological activity. [10] A huge number of bis-phenanthridine derivatives were prepared with the aim of not only enhanced affinity due to the bis-intercalation into DNA/RNA but also with the idea of introducing selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In addition, it was shown that the chemical modulation of the ethidium substituents is a profitable option to tune the nucleic acid recognition properties of phenanthridine dyes. [4] Very recent reports about numerous applications point toward versatility of the phenanthridine core, [5][6][7][8][9] including even intriguing biological activity. [10] A huge number of bis-phenanthridine derivatives were prepared with the aim of not only enhanced affinity due to the bis-intercalation into DNA/RNA but also with the idea of introducing selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem, Clement et al recently described the synthesis and the antitumoral activity of 6-aminobenzo[c ]phenanthridine derivatives, also bearing a phenyl group on C-11. These molecules were shown to be very potent agents against various tumour cell lines [19]. Compared to our BZP series, the iminium function, characterized by its positively charged nitrogen, has been replaced by an amidine group, potentially bearing a positive charge.…”
Section: Lipophilicitymentioning
confidence: 97%
“…苯甲醛中取代基 R 为供电子烷氧基或卤素原子时 对整个反应的得率没有影响 [53] . 但是以甲醛为原料时 目标产物 6-氨基-11,12-二氢苯并啡啶(118)的得率降低 至 11%, 影响 118 得率的原因仍然有待研究.…”
Section: Bischler-napieralski 环合反应unclassified